Spatiotemporal Dynamics of Nitrous Oxide Emission Hotspots in Heterogeneous Riparian Sediments. Issue 12 (14th December 2021) - Wallace, Corey D.; Tonina, Daniele; McGarr, Jeffrey T.; de Barros, Felipe P. J.; Soltanian, Mohamad Reza
Abstract: Nitrous oxide (N2 O) is a potent ozone‐depleting greenhouse gas produced by incomplete denitrification. Recent works on riverine N2 O emissions focus mainly on contributions from in‐channel, benthic, and fluvial hyporheic environments under assumptions of steady‐state conditions and homogeneous sediment hydraulic conductivity ( K ). However, riparian floodplains are also a potentially important N2 O source characterized by complex sediment heterogeneity and dynamic surface and groundwater interactions. We use numerical flow and reactive transport models to investigate the influence of complex sedimentary architecture and high‐flow events (e.g., storms) on N2 O production. We interpret the correlation between flow and solute fields with the flow topological Okubo‐Weiss metric (OW) and the scalar dissipation rate weighted by soil organic matter (OM) fraction and soil saturation. We model a heterogeneous riparian floodplain based on field observations from the Theis Environmental Monitoring and Modeling Site, Ohio, USA. N2 O production is greatest within intermediate‐ K sediments (e.g., sands) where denitrification rates are highest, and emissions increase by more than an order of magnitude during storms. Sensitivity analysis reveals that the denitrification rate is most influential for N2 O flux, accounting for nearly 46% of the variance in production rates. Denitrification rates adapt to spatial changes in the flow topology (measured by OW) related to sediment heterogeneity and are strongly influenced by subsurface mixing dynamics. Mixing is greatest in shear strain‐dominated regions, while vorticity promotes OM dissolution and prolongs residence times. Accurate lithologic representation is imperative for characterizing subsurface N2 O production dynamics, especially given growing concern regarding climate change driven hydrologic changes within watersheds worldwide. Key Points: Subsurface N2 O production increases in response to storms, but sediment heterogeneity controls the location and magnitude of emissions Accurate representation of heterogeneity is important for characterizing subsurface nitrogen transformations and N2 O production dynamics Heterogeneity introduces shear into the groundwater flow topology, enhancing mixing and increasing the spatial extent of denitrification